Safety culture at primary healthcare level - Klemenc-Ketiš, Zalika (Zdravstveno varstvo, 2020)
Introduction: An effective leadership is critical to the development of a safety culture within an organization. With this study, the authors wanted to assess the self-perceived level of safety culture among the employees with a leadership function in the Ljubljana Community Health Centre. Methods: This was a cross-sectional study in the largest community health centre in Slovenia. We sent an invitation to all employees with a leadership role (N=211). The Slovenian version of the SAQ - Short Form as a measurement of a safety culture was used. The data on demographic characteristics (gender, age, role, work experience, working hours, and location of work) were also collected. An electronic survey was used. Results: The final sample consisted of 154 (69.7%) participants, out of which 136 (88.3%) were women. The mean age and standard deviation of the sample was 46.2-10.5 years. The average scores for the safety culture domains on a scale from 1 to 5 were 4.1-0.6 for Teamwork Climate, Safety Climate, and Working Conditions and Satisfaction, 3.7-0.5 for Perception of Management, 3.6-0.4 for Communication, and 3.5-0.6 for Stress Recognition. Conclusion: The safety culture among leaders in primary healthcare organizations in Slovenia is perceived as positive. There is also a strong organizational culture. Certain improvements are needed, especially in the field of communication and stress recognition with regards to safety culture.
Keywords: kultura varnosti; organizacijska kultura; organizational culture; primarna zdravstvena raven; primary healthcare; safety culture